Help-seeking behaviours of abused women in Singapore - Chua, Eileen Chiew Hoon. (2008)
This study explored the help-seeking behaviour of abused women in Singapore in terms of their perferred soureces of help, possible barriers they faced in seeking help and their reasons for seeking help. Their help-seeking behaviour was examined across severity of physical and non-physical abuse, as well as their sociodemographic characteristics.